2012
DOI: 10.1016/j.bbalip.2011.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Long chain polyunsaturated fatty acid synthesis in a marine vertebrate: Ontogenetic and nutritional regulation of a fatty acyl desaturase with Δ4 activity

Abstract: Solea senegalensis is an unusual marine teleost with very low dietary requirement for longchain polyunsaturated fatty acids (LC-PUFA) during early development. Aquaculture is rapidly becoming the main source of health-beneficial fish products for human consumption. This, associated with limited supply of LC-PUFA-rich ingredients for fish feeds, render S. senegalensis a highly interesting species in which to study the LC-PUFA biosynthesis pathway. We have cloned and functionally character -3 series) and elovl5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
105
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 52 publications
(48 reference statements)
7
105
0
8
Order By: Relevance
“…A discrete Δ5 Fad has only been isolated from Atlantic salmon although bifunctional Δ6Δ5 Fads have been characterised in zebrafish, rabbitfish, Siganus canaliculatus and Mexican silverside, Chirostoma estor (Hastings et al, 2001;Li et al, 2010;Monroig et al, 2014). The presence of Δ4 Fad enabling direct production of 22:6n-3 from 22:5n-3 has been demonstrated in rabbitfish, Senegalese sole, Solea senegalensis and Mexican silverside, Chirostoma estor (Li et al, 2010;Morais et al, 2012c;Monroig, et al, 2014). The Sprecher shunt pathway via C24 fatty acid intermediates has been shown in trout (Buzzi et al, 1997) and the Δ6 Fad of Atlantic salmon and zebrafish can operate on both C18 and C24 fatty acids .…”
Section: Discussionmentioning
confidence: 99%
“…A discrete Δ5 Fad has only been isolated from Atlantic salmon although bifunctional Δ6Δ5 Fads have been characterised in zebrafish, rabbitfish, Siganus canaliculatus and Mexican silverside, Chirostoma estor (Hastings et al, 2001;Li et al, 2010;Monroig et al, 2014). The presence of Δ4 Fad enabling direct production of 22:6n-3 from 22:5n-3 has been demonstrated in rabbitfish, Senegalese sole, Solea senegalensis and Mexican silverside, Chirostoma estor (Li et al, 2010;Morais et al, 2012c;Monroig, et al, 2014). The Sprecher shunt pathway via C24 fatty acid intermediates has been shown in trout (Buzzi et al, 1997) and the Δ6 Fad of Atlantic salmon and zebrafish can operate on both C18 and C24 fatty acids .…”
Section: Discussionmentioning
confidence: 99%
“…First, the so-called "Sprecher pathway" involves two sequential elongation steps from EPA to 24:5n-3 and a subsequent ⌬ 6 desaturation to 24:6n-3, followed by peroxisomal chain shortening ( 3 ). Second, a more direct pathway has been postulated in some marine fi sh that involves elongation of EPA to docosapentaenoic acid (22:5n-3) followed by ⌬ 4 desaturation to DHA ( 4,5 ).Dietary PUFAs are essential in fi sh, although requirements vary with species ( 6, 7 ). Generally, C 18 PUFAs can satisfy essential FA requirements of freshwater and salmonid species, but most marine fi sh have a requirement for LC-PUFAs such as EPA and DHA ( 8 ).…”
mentioning
confidence: 99%
“…Different fish species have different ways of increasing PUFA to maintain the structural and functional integrity of their cellular membranes (Farkas et al, 2001). Recently, this widely accepted paradigm was revised after the discovery of another pathway of synthesis of LC-PUFA in two marine vertebrates, Siganus canalicalatus (Li et al, 2010) and Solea senegalensis (Morais et al, 2012) so, further investigations would be needed to find different biosynthesis pathways. After observing the great ability of the eel to synthesize PUFA in the liver during spermiation, studies on the isolation, cloning, and characterization of European eel fatty desaturases and elongases should be an important focus of future research.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1. Bioconversion ability of 18:3-n3 (Kanazawa et al, 1979) In recent years, numerous studies on the abilities of fatty acid bioconversion in freshwater and marine fish have been carried out (Monroig et al, 2012Morais et al, 2012;Fonseca-Madrigal et al, 2014). It has been demonstrated that a freshwater fish may have a marine pattern of fatty acid elongation and desaturation or vice versa.…”
Section: Essential Fatty Acids Of Marine and Freshwater Fishmentioning
confidence: 99%
See 1 more Smart Citation